Measuring the middle class in middle income countries - Rebecca Rasch (Luxembourg Income Study (LIS), 2014)
This research aims to compare different methods of measuring the middle class in middle-income countries. I compare income-based measures to socio-economic measures, using both per capita and equivalized incomes. First I calculate the size of the middle class using the different measures in six countries: India, South Africa, Peru, Colombia, Guatemala and Mexico. Next I explore whether a socio-economic measure of the middle class is significantly correlated with the income-based measure. I examine the differences across the measures and suggest that per-capita, income-based measures commonly used by international development institutions such as the World Bank, may be insufficient for meaningfully identifying the middle class in middle-income countries. Instead I advocate for the adoption of a hybrid measure, which uses absolute, equivalized income, education and occupation to assign households middle class status in middle-income countries.
Keywords: 330